PRESCRIPTION OF ANIMALS IN THE WRITINGS OF RUSKIN BOND - Dhaka, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nobody knows the source or person who showered a hidden blessing on mankind by introducing the art of story-telling. The age-old traditions of tell tales served various purposes simultaneously. At one side tales were the source of entertainment, sharing and exchanging of thoughts at another side tell tale became the medium of spread of education, morality and cultural heritage, which prevailed from time to time. Thus people made this form of expression widely popular and made its reach from door to door, from villages to towns, from town to cities. Later on this tell tale became a variety of literature. From Chaucer’s Canterbury Tales or rather age before than that to modern times the role of stories has become very prominent, significant and popular.